Excellent electric field-induced strain with high electrostrictive and energy storage performance properties observed in lead-free Bi0.5(Na0.84K0.16)0.5TiO3-Ba(Nb0.01Ti0.99)O3-BiFeO3 ceramics - Supalak Manotham (2019)
© 2019 Elsevier B.V. In this research, ceramics with a high electromechanical strain based on the composition (1-x)[0.97Bi0.5(Na0.84K0.16)0.5TiO3-0.03Ba(Ti0.99Nb0.01)O3]-xBiFeO3 or (1-x)[BNKT-0.03BNbT]-xBFO (with x = 0, 0.03, 0.05, 0.07, and 0.09 mol fraction) were investigated. All compositions were synthesized via a conventional solid-state mixed oxide method. The effects of the addition of BFO on the phase structure, dielectric, ferroelectric, and piezoelectric properties and electric field-induced strains behavior of BNKT-0.03BNbT ceramics were systematically studied in this work. X-ray diffraction (XRD) analysis revealed that all ceramics exhibited a pure perovskite structure. The coexistence of rhombohedral (R) and tetragonal (T) phases was observed for all compositions. The electric field-induced strain increased with increasing BFO content and attained a maximum value of Smax = 0.65% and d*33 = 1161 pm/V (@40 kV) for the composition x = 0.05 at room temperature (RT). The bipolar strain behavior exhibited minimal asymmetry and a low driving electric field. The composition also exhibited a high electrostrictive response (Q33 ∼ 0.039 m4/C2). In addition, the x = 0.09 composition showed excellent energy storage properties, with an energy storage density of 0.91 J/cm3 at 125 °C, high normalized energy storage density (∼0.14 μC/mm2), thermal stability (7% for 75-150 °C) and energy storage efficiency (η = 87% @125 °C). These results suggest that the (1-x)[BNKT-0.03BNbT]-xBFO ceramics are promising as lead-free piezoelectric material candidates, and are also suitable for both actuator and high temperature energy storage applications.